Does your smartphone “know” your social life?: A methodological comparison of day reconstruction, experience sampling, and mobile sensing - Roos, Yannick; Krämer, Michael; Richter, David; Schoedel, Ramona; Wrzus, Cornelia (Advances in methods and practices in psychological science, 2023)
Mobile sensing is a promising method that allows researchers to directly observe human social behavior in daily life using people’s mobile phones. To date, limited knowledge exists on how well mobile sensing can assess the quantity and quality of social interactions. We therefore examined the agreement among experience sampling, day reconstruction, and mobile sensing in the assessment of multiple aspects of daily social interactions (i.e., face-to-face interactions, calls, and text messages) and the possible unique access to social interactions that each method has. Over 2 days, 320 smartphone users (51% female, age range = 18-80, M = 39.53 years) answered up to 20 experience-sampling questionnaires about their social behavior and reconstructed their days in a daily diary. Meanwhile, face-to-face and smartphone-mediated social interactions were assessed with mobile sensing. The results showed some agreement between measurements of face-to-face interactions and high agreement between measurements of smartphone-mediated interactions. Still, a large number of social interactions were captured by only one of the methods, and the quality of social interactions is still difficult to capture with mobile sensing. We discuss limitations and the unique benefits of day reconstruction, experience sampling, and mobile sensing for assessing social behavior in daily life.